Evaluation study of the classroom based intervention (CBI®) for children exposed to armed conflict in western Nepal. - Jordans,Mark (2007)
ABSTRACT: Background: Little is known about the effectiveness of psychosocial interventions for children in areas of armed conflict, especially in non-Western countries. One of such interventions is the Classroom-Based psychosocial Intervention (CBI®), a 15-session expressive behavioral intervention that aims to reduce potentially harmful traumatic stress symptoms and increase children's capacity to solve problems, maintain prosocial attitudes and sustain self-esteem as well as hope for the future. This intervention has been implemented, by and through Save the Children US, in Nepal since 2002. Evaluations and subsequent adaptations to the intervention and implementation of the intervention have been made. Anecdotal information from children, teacher, parents and community members has been very positive about CBI. However, a structural scientific (evidence based) evaluation has not been conducted yet. This research looked into the impact of CBI for children affected by the armed conflict in Nepal. Research Methods: Through a randomized controlled trial we have compared pre-, and postintervention levels of symptoms and functioning of 161 children that received CBI (treatment group) with 164 children that did not receive CBI (control group). Children were between 11-14 years old. The research was conducted in 4 mid-Western Terai districts in Nepal. Groups were compared on mental health indicators (depression-, anxiety-, and post-traumatic stress symptoms), general psychosocial wellbeing indicators (emotional problems, peer problems, hyperactivity and conduct problems), resilience indicators (prosocial behavior and hope) and daily functioning. Almost all children completed the research (2 children did not complete post test measurement). Research Findings: Research shows that baseline levels of psychosocial problems and impairment in daily functioning are elevated. On most of the psychosocial well-being indicators the total study group (n=325) has high mean score, indicating treatment. Especially levels of anxiety symptoms, emotional difficulties and PTSD symptoms are elevated. This finding is an important argument for continued attention to psychosocial and mental health programming. The research shows a number of significant positive changes in psychosocial well-being, attitude and functioning. The level of this impact is moderate. For more specific complaints such as PTSD and aggression the intervention did not sort effect. CBI is a safe and moderately effective intervention for war affected children to improve general psychosocial well being. It is important to note that these results were established in a situation of ongoing instability. Regarding the positive impact, CBI appears to sort moderate effect on: 1) Reducing the level of children's impairment in daily functioning 2) Reducing depression complaints 3) Reducing experienced difficulties of children related to hyperactivity, peer problems, emotional problems and conduct problems 4) Improving the children's level of prosocial behavior It needs to be noted that the treatment group saw a significantly bigger change on anxiety reduction, but the effect size of this change was too small to have clinical relevance.No important gains from CBI were gained in reducing post-traumatic symptoms, aggression complaints and feelings of hope. The pre-, and post-intervention change scores on each of these measures did not differ between treatment and control group. It is important to note here that PTSD complaints did reduce significantly over time, but reduced in the same level in both groups. Similarly, feelings of hope did increase over time, but similarly in both groups. There was no significant change in self-reported aggressive behavior in both groups. Conclusion: In conclusion the study shows that CBI is a safe and positive intervention, but sorts not more then moderate effects. Offering CBI for children with psychosocial problems in areas of armed conflict holds potential, mainly for improving generic emotional and functional well-being. Recommendations and clinical implications are discussed, mainly discussing the need for re-focusing and adapting the intervention to better match the intervention's potential with problems and needs. Furthermore, it needs to be planned in addition to other interventions, especially for children with more specific behavioral and PTSD complaints. Further research is needed to determine the possible preventive effect of the intervention, as well as the relation between improved daily functioning and changes in mental health status.